Nursing Process Design of Intravenous Thrombolysis in Elderly Patients with Acute Cerebral Infarction. (30th July 2022) - Xia, Yuanyuan; Chen, Yuan; Xia, Rucui; Chen, Yunyun; Gu, Qian; Lu, Qing
Abstract : The economy of contemporary society is developing rapidly and the society is making continuous progress. The population is aging and diet structure is also adjusted. Acute cerebral infarction(ACI) in the elderly has become a common disease that seriously threatens the health of the elderly. Therefore, research on nursing of senile ACI is of great significance. Nursing is essential in the thrombolytic therapy of cerebral infarction. This article aims to study the process design of intravenous thrombolytic nursing for elderly patients with ACI and the conclusions are as follows: the nursing process has a good nursing effect. This increased the Barthel index of elderly patients with ACI after intravenous thrombolysis care by 15.8 compared with that before care. Compared with the traditional nursing mode, the nursing course and cost are significantly reduced.